TALES OF THE GREEK HEROES - Green, Roger Lancelyn; Fish, Hannah; Pitts, Sorrel ([London] UK : PENGUIN BOOKS, 2020)
Penguin Readers is a graded reading series for English Language Teaching (ELT) markets, designed for teenagers and young adults learning English as a foreign or second language.
Includes question and excercises
Keywords: Readers -- Mythology, Greek; Heroes -- Mythology; Readers